Forensic psychology: an inside perspective on criminal thinking and behavior - Cairns, Kenneth B. (Sage, 2023)
"Forensic Psychology: An Inside Perspective on Criminal Thinking and Behavior offers undergraduates a concise, accessible introduction to the field of forensic psychology. With more than 20 years of experience as a forensic psychologist working with incarcerated people, Dr. Kenneth B. Cairns provides a balance between not just forensics and psychology, but also between theory and practical application. Grounded in the cognitive-behavioral approach and evidence based-practices and research, this text will focus on often-overlooked areas, such as the experiences of victims and first responders and the psychopathy of individuals convicted of mass murder, spree killing, and serial killing"--